Zimbabwean Manufacturing Firms’ Propensity and Intensity to Export in the Post Zimbabwean Dollar Era - Mugumisi, Nathan (Journal of Economics and Behavioral Studies, 2018)
After the adoption of the multicurrency system in 2009 Zimbabwe’s macroeconomic environment stabilized but the new economic order exposed the economy to a crippling liquidity crisis. Exports remain the only sustainable solution to Zimbabwe’s liquidity crisis in the short to medium term given the current sanctions that limits other international capital flows. This study sort to understand the factors that determine Zimbabwean manufacturing firms’ likelihood and intensity to export. The study a was based on panel data from a 19 manufacturing firms listed on the Zimbabwe Stock Exchange over the period 2009 to 2017. The propensity and intensity to export was estimated using the logit and Tobit regression models respectively. Bigger firms and firms that engage in research and development had a high propensity to export. Foreign owned firms and firms that engage in research and development had a high intensity to export, while those with high domestic turnover tended to export less. The appreciation of the USD increased Zimbabwean manufacturing firms’ propensity and intensity to export. We urge the policy makers to design investment laws that attract foreign investors, and managers to prioritize research and development. We also recommend firm managers to take advantage of periods of currency appreciation to recapitalize at a cheaper cost and export more goods since Zimbabwe’s manufacturing production is highly import dependent.